Ekstrak Daun Kelor (Moringa Oleifera Lamk) dalam Menurunkan Kadar Glukosa Darah pada Tikus (Rattus novergicus) - Mursito, S., Mursito, S.; Lilies, Bialangi; Mawaddah, Hayyatun (Fakultas MIPA UNM, 2020)
Abstract. The purposes of this study were: 1) obtain information on the benefits of Moringa leaf extract which has the effectiveness in reducing blood glucose levels. specifically on Rattus norvegicus, 2) obtaining information about the concentration of Moringa oleifera leaf extract) has effectiveness in reducing blood glucose levels, specifically on Rattus norvegicus. Research conducted in the Laboratory of Biology Education Study Program at the Tadulako University FKIP in May until August 2018 and is an experimental study using the RAL method. The independent variable In this study was Moringa oleifera leaf extract, and the dependent variable was the glucose level on Rattus Norvegicus. Data analysis in this research was carried out using, analysis of quantitative Anava data with the help of SPSS Version18. Significant results of an analysis of variance (ANAVA) obtained a significance value of 0,000<Î± (0.05), which means rejecting Ho and accepting H1. Thus it can be explained that Moringa leaf extract has a significant effect on the reduction in blood glucose levels in rats (Rattus governors). When seen in the results of the analysis of the advanced test using the Duncan test, the best concentration in reducing glucose levels is on the M4 treatment, with Duncan test results that are different from the other, amounting to 113.40. Keywords: moringa oleifera lamk, blood glucose, rattus novergicus.